Aggregator Backend API With KrakenD - Fikri Muhaffizh Imani (International ABEC, 2022)
Implementation of API Gateway to secure and expose backend API as an endpoint that can be accessed by the client is ideal step in developing an integrated system. The client makes a request through an endpoint exposed by API Gateway to get the data needed to display a web page, but the server load will increase if the page requires data from several endpoints that require multiple requests to be made to the server. Vertical scaling can be applied to increase server resources in order to handle these requests, but this solution costs a lot of money. This research was conducted to overcome the problem of multiple requests by clients without having to do vertical scaling by implementing KrakenD as an aggregator backend API to combine several backend API into one and expose the combined results back into a new endpoint. Based on the results of the study, aggregation on several API backends was able to reduce 75% of the request load to the server. This solution can become novel consideration in building an information system that requires data from several different backend API.